Use of Fight Category Pencak Silat Techniques at the National Student Sports Week - Fajar Syamsudin; Aziz Amrulloh; Nur Subekti; Muhad Fatoni; Muhammad Bakhtiar Subardi (Altius: Jurnal Ilmu Olahraga dan Kesehatan, 2023)
The pencak silat techniques used in pencak silat competitions in the sparring category are very diverse, until now there has been no research that provides evidence of which techniques are often used in matches, from punches, kicks to slams. This study aims to determine the percentage of the use of fighting category pencak silat techniques in one of the prestigious pencak silat competitions, namely the National Student Sports Week. The method used is descriptive quantitative, the results of the research data are in the form of percentage figures for the use of techniques. The selected subjects were all athletes who competed in the championship, starting from the preliminary to the final with a total of 180 matches. Data collection used a laptop media device to view match recordings, then filled in the tally form was carried out by 4 people, 2 people to calculate the acquisition of the blue corner athletes, 2 people to calculate the acquisition of the red corner athletes. This calculation is done carefully, it takes 2 months. After all calculation forms have been collected, enter the data obtained for the formula into Microsoft Excel to determine the percentage of the technique used. Conclusion: Ranking techniques that are often used in the 2017 National Student Sports Week are 1. Crescent Kick (26.66%), 2. Punch (14.52%), 3. Front Kick (14.16%), 4. Side Kick (12.07%), 5 , Cut (9.97%), 6. Throwback (9.55%), 7. Block (7.50%), 8. Avoidance (4.20%) 9. Sweep (1.00%), and 10. Back kick (0.37%). Techniques that have an attacking type are techniques that are often used, including sickle kicks, followed by punches, then front kicks and side kicks. Even so, defensive techniques also have a fairly high percentage too, though not as high as attacking techniques. So it is also important for coaches to prepare both techniques, both attack techniques and defensive techniques.